The Economic Implications of Cryptocurrency Adoption in Emerging Markets - Irawan, Nico; Srisuk, Prattana (JMM17 : Jurnal Ilmu ekonomi dan manajemen, 2025)
This study examines the economic implications of cryptocurrency adoption in emerging markets, with particular emphasis on its potential to promote financial inclusion, reshape monetary policy frameworks, and facilitate cross-border trade. Emerging economies face persistent challenges such as limited access to banking services, high remittance costs, and vulnerability to currency instability, all of which create fertile ground for the adoption of digital assets. Cryptocurrencies, supported by blockchain technology, offer decentralized alternatives that can bypass traditional financial intermediaries and provide low-cost, efficient, and accessible financial services to underserved populations. At the same time, their integration into fragile financial systems raises important concerns about volatility, regulatory uncertainty, and the erosion of monetary sovereignty. To address these dynamics, this research adopts a mixed-methods approach that combines econometric modeling with qualitative policy analysis. Panel regression and instrumental variable techniques are employed to evaluate the relationship between cryptocurrency adoption, financial inclusion, and macroeconomic indicators across a sample of emerging markets from 2015 to 2025. Complementary qualitative data, including policy reports and expert interviews, are analyzed thematically to capture the perspectives of regulators, entrepreneurs, and development practitioners. The findings reveal that cryptocurrency adoption contributes positively to financial inclusion and lowers remittance transaction costs, particularly in countries with large unbanked populations and remittance-dependent households. However, widespread adoption also introduces risks, including exchange rate volatility, reduced effectiveness of monetary policy, and heightened exposure to illicit financial activities. By integrating empirical evidence with policy insights, this study advances the literature on digital finance and offers context-sensitive recommendations for the sustainable adoption of cryptocurrencies in developing economies.